Explaining Unemployment Duration in Australia - Carroll, N (My University, 2004)
What influences the probability that someone will leave unemployment? Informed by a search-theoretic framework and allowing for exits to not in the labour force and employment, I examine what influences the probability that somebody will leave unemployment. The unemployment data used are derived from the retrospective work history information from the first two waves of the Household, Income and Labour Dynamics in Australia Survey. I find that variables that increase wage offers and lower reservation wages are associated with shorter durations of unemployment and that exit rates from unemployment appear to remain steady initially with duration before declining relatively sharply.
Centre for Economic Policy Research, Australian National University, Discussion Paper
Keywords: Employment -- Unemployment; Employment; Labour market; Employment and unemployment